Performance Indicators and Trends of Small and Medium Enterprises of Economic Development in India - Mr.E.Manikandan; Dr.C.Sengottuvel (Zien Journals, 2021)
Small and Medium Enterprises (SME) play pivotal role in Indian manufacturing sector and have become engine of economic growth in India with their effective, efficient, flexible and innovative entrepreneurial spirit. It is generating the highest rates of employment growth and account for a major share of industrial production. It is estimated that Small and Medium Enterprises account for almost 90% of industrial units in India and 40% of value addition in the manufacturing sector. This paper closely analyses the growth and development of the Indian Small and Medium Enterprises sector from opening of the economy in 1991. The Small and Medium Enterprises Act, 2006 is intended to boost the sector. The provisions of the Act are examined closely. In India SME sector is used as an efficient tool of progress. The recent data available indicate that the SME sector if India that accounts for 96% of the country’s industrial units with 60% value addition in the manufacturing sector, shares 36% of the country’s total export, contributes 9.54% GDP, employs nearly 10 lakhs per annum, registering a sectored growth rate of 9.24% as against 8.7% of the country’s over-all industrial growth rate during 2018-19. During the 12th plan 6.7 million new jobs were created by the sector, while 8.6 million additional jobs are expected to be creating by the 13th plan. The final part provides some future trends and Sustainable performance indicates of small and medium enterprises
Keywords: Sustainable Growth; development; SMEs; manufacturing